Preconceptional immunity and congenital Cytomegalovirus infection - a serologic pitfall - Ferreira,Joana da Silva (2021)
Abstract Congenital cytomegalovirus infections are the most prevalent intrauterine infections worldwide and result from maternal primary or non-primary infections. Diagnosis of primary cytomegalovirus infection during pregnancy is considered reliable and mainly relies on maternal serology. However, diagnosis of non-primary cytomegalovirus infection is more questionable. Herein is reported the case of a 34-week-old male newborn with congenital cytomegalovirus infection of a mother with preconceptional immunity. The organism was identified in urine by polymerase chain reaction in the first week of life. Maternal peripartum serology was the same as prior to conception. This case highlights the pitfalls of cytomegalovirus serology interpretation in non-primary infection during pregnancy. Clinicians should be aware of this and consider congenital cytomegalovirus infection, particularly when suggestive signs are present.